Identification and Risk Mitigation of Zakat Fund Management Based On COSO ERM at LAZ Yakesma East Java - Ali Fikri, Roha Dewi; Evrytanadha, Ayiek; Nabilah Aini, Saqofa (Program Studi Manajemen Zakat dan Wakaf, 2025)
This study aims to identify and mitigate risks in zakat fund management at LAZ Yakesma East Java using the COSO Enterprise Risk Management (ERM) framework, which represents a novel application in the context of Islamic philanthropy. A descriptive-qualitative method was employed through interviews, institutional documents, and secondary reports to explore how zakat governance can be strengthened. Findings reveal three major risks: first, the presence of anonymous muzakki, which account for nearly half of total donors and create obstacles in reporting, auditing, and compliance; second, competition with more established zakat institutions, such as Dompet Dhuafa and Rumah Zakat, that affects public trust and donor loyalty; and third, limited fundraising capacity, which reduces program scope and innovation. To address these challenges, Yakesma has initiated mitigation strategies, including digital donation platforms with identity verification, financial transparency through online reporting, and diversification of fundraising methods. The application of the COSO ERM framework demonstrates its relevance in systematically identifying, assessing, and managing risks while ensuring sharia compliance and accountability. This study contributes to the literature by showing how risk management tools can be adapted to strengthen governance, enhance donor trust, and optimize the socio-economic impact of zakat.